PEMANFAATAN LIMBAH DAPUR MENJADI PRODUK BERHARGA YANG BERNILAI EKONOMIS DAN MEMILIKI NILAI JUAL (PUPUK KOMPOSTER ORGANIK) - Amri, Haeril; Santika, Dea; jannah, Miftahul; Pamungkas, Firga Raditya; Ulfhani, Annisa; lesstari, Indria; Tunngga, Prayoga Purnama; Najmatunnufus, Najmatunnufus; Pratama, Fikri Hadi (Universitas Mataram, 2024)
Composter fertilizer can be one way to overcome the problem of environmental pollution by reducing organic waste and utilizing it into useful products. Through the PMD KKN (Village Community Empowerment) service activity carried out by students of the University of Mataram aims to invite the village community to utilize and process waste into new useful products. This activity was held on July 25, 2024 at 09.00-11.00 WITA which was held at SDN 1 Jelateng, Tumpak Village, Pujut District, Central Lombok Regency. The method used in the implementation of this KKN service activity is socialization and education about making composter fertilizer. It is hoped that this activity can make the community educated so as to increase participation in sustainable waste management. The implementation of this activity received a positive response from the enthusiastic community who could help reduce the volume of waste generated from kitchen activities. The result of this KKN service activity is to increase public awareness about the importance of maintaining environmental cleanliness, how to manage organic waste, and a better understanding of the community about processing kitchen organic waste into composter.